EVALUASI KUALITAS AIR SUNGAI-SUNGAI DI KAWASAN DAS BRANTAS HULU MALANG DALAM KAITANNYA DENGAN TATA GUNA LAHAN DAN AKTIVITAS MASYARAKAT DI SEKITARNYA - Yetti, Elvi; Soedharma, Dedi; Hariyadi, Sigid (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2011)
Brantas River that is located at Upper Brantas River Basin Area has been polluting that is noted by poluttion that taking place at Karangkates and Sengguruh Reservoir. Development of people and industries around Malang Upper Brantas River Basin Area since 2000, leading to increasing of river water using and pollution, particularly organic pollution. This research evaluated river water quality at Malang Upper Brantas River Basin Area, refered to water quality standard inserted on Governmental Regulation Number 82 / 2001 (PP No. 82 tahun 2001) and observed its relation to land use system and its surrounding people activity. Water quality is observed at 18 station focusing on physical parameters such as temperature, conductivity, suspended solid, and chemical parameters such as pH, DO, BOD, COD, N-nitrate, total nitrogen, orthophosphate and total phosphorous. Furthermore, water quality status is determined by using of pollution index methode, based on Environment Ministerial Regulation Number 115 / 2003 (Kep. Men. LH No. 115 tahun 2003). Evaluation result was related to land use system at Upper Brantas River Basin Area and its surroundings people activity. Evaluation result showed that, water quality has been decreasing at that area compared with the year of 1997-2002, and furthermore almost at all stations the value of COD has exceeded maximum limit threshold. Determination of water quality status also showed that all rivers at Upper Brantas River Basin has been polluted, majority with medium polutted grade. Research the result also showed that river water quality at Malang Upper Brantas River Basin is influenced by land use system and its surroundings people activity, particuarly by industries located along the river basin. Key Words: Evaluation of River Water Quality, Upper Brantas River Basin, land use system, surroundings people activity